Effects Of Droplet-Vitrification Cryopreservation Method On Ludisia Discolor For Long-Term Germplasm Conservation - Burkhan, Hazirah (2024)
Ludisia belongs to a group of slow-growth terrestrial orchids cultivated for their attractive ornamental leaves, commonly referred to as ‘Jewel Orchids’. They are steadily dwindling in their natural population through habitat loss and indiscriminate collection of wild orchids. Therefore, cryopreservation as a long-term storage approach offers a complementary conservation strategy that safeguards against accidental loss. Although some cryopreservation methods have been developed for several genera of the Orchidaceae family, the cryopreservation method for Ludisia species has not been documented before. Therefore, this study reported the first attempt of long-term storage of L. discolor, using a droplet-vitrification method. The present study sought to examine the effects of cryopreserving L. discolor orchid supported with qualitative analyses using microscopy, biochemical, and molecular. Critical parameters such as preculture sucrose concentrations and durations, plant vitrification solution 2 (PVS2) durations and temperatures, growth recovery medium, and different light-emitting diode (LED) spectra were assessed. The survivability of axillary bud was determined using 2,3,5-triphenyltetrazolium chloride (TTC) spectrophotometric analysis and visual inspection.